Strategi Inovatif dalam Program Pemulihan Ekonomi: Analisis Kegiatan untuk Meningkatkan Performa Sektor Ekonomi - Elamugi Setyautami; Kiskendra Citra Hati; Febri Kurniawan (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2024)
Economic recovery amidst global challenges requires the right strategy and innovation so that the economic sector can recover optimally. This article analyzes various strategies and innovations implemented in activity programs to improve the performance of the economic sector. This study uses a descriptive analytical approach by examining several programs and activities that have been implemented in various countries. The results of the analysis show the importance of adaptation strategies, technological innovation and collaboration between stakeholders in accelerating post-crisis economic recovery. These findings provide guidance for governments, companies and related institutions to design and implement effective and sustainable economic recovery programs.